NIN Acts as a Network Hub Controlling a Growth Module Required for Rhizobial Infection. Issue 4 (1st February 2019) - Liu, Cheng-Wu; Breakspear, Andrew; Guan, Dian; Cerri, Marion R.; Jackson, Kirsty; Jiang, Suyu; Robson, Fran; Radhakrishnan, Guru V.; Roy, Sonali; Bone, Caitlin; Stacey, Nicola; Rogers, Christian; et al.
Abstract : The RWP-RK transcription factor Nodule Inception regulates genes required for rhizobial infection, including Rhizobium Polar Growth (RPG) and genes for nutrient (N, P, and S) uptake and assimilation. Abstract: The symbiotic infection of root cells by nitrogen-fixing rhizobia during nodulation requires the transcription factor Nodule Inception (NIN). Our root hair transcriptomic study extends NIN's regulon to include Rhizobium Polar Growth and genes involved in cell wall modification, gibberellin biosynthesis, and a comprehensive group of nutrient (N, P, and S) uptake and assimilation genes, suggesting that NIN's recruitment to nodulation was based on its role as a growth module, a role shared with other NIN-Like Proteins. The expression of jasmonic acid genes in nin suggests the involvement of NIN in the resolution of growth versus defense outcomes. We find that the regulation of the growth module component Nodulation Pectate Lyase by NIN, and its function in rhizobial infection, are conserved in hologalegina legumes, highlighting its recruitment as a major event in the evolution of nodulation. We find that Nodulation Pectate Lyase is secreted to the infection chamber and the lumen of the infection thread. Gene network analysis using the transcription factor mutants for ERF Required for Nodulation1 and Nuclear Factor-Y Subunit A1 confirms hierarchical control of NIN over Nuclear Factor-Y Subunit A1 and shows that ERF Required for Nodulation1 acts independently to control infection. We conclude that while NIN shares functions with other NIN-Like Proteins, the conscription of key infection genes to NIN's control has made it a central regulatory hub for rhizobial infection.